Elucidating mother to offspring transmission of chronic wasting disease using a transgenic mouse model - Willingham, Kassandra, author; Mathiason, Candace, advisor; Zabel, Mark, committee member; Suchman, Erica, committee member; Winger, Quinton, committee member (Colorado State University. Libraries, 2016)
Chronic wasting disease (CWD) is a transmissible spongiform encephalopathy (TSE), or prion disease, of free-ranging and farmed cervids (deer, elk and moose). CWD is the only TSE in a wildlife population, which was initially discovered in a captive mule deer herd in a study shared between Colorado State University and University of Wyoming in 1967. CWD is the most readily transmitted of all the prion diseases and since its discovery has been identified in cervid populations in 24 states, 2 Canadian provinces, and the Republic of Korea. Horizontal transmission of prion diseases is thought to account for its exceptional transmission efficiency [2-10]. Recent studies published by our group provide evidence that transmission from mother to offspring may also be a contributing factor. In the work of this thesis, we employed a transgenic mouse system that expresses the cervid prion protein Tg(CerPrP-E226) to help elucidate the role of mother to offspring CWD transmission via hemochorial placentation. Females were inoculated with known CWD-positive material and subsequently bred with CWD-naïve males at various timepoints post inoculation to investigate if maternal/vertical transmission occurs in this host, as well as to further understand how this might occur. We examined the likelihood of prion trafficking in utero by analysis of mother: offspring pairs at different timepoints in CWD-infection and gestation, in addition to looking for infectious prions in milk collected from CWD-positive dams. We have demonstrated that CWD-infected Tg(CerPrP-E226) females successfully breed and bear offspring irrespective to TSE disease stage. Offspring born to CWD- infected females did not exhibit signs of TSE disease and lacked detectible PrPres via conventional methodologies. Interestingly, conversion competent prions were identified in the brains and spleens of offspring by highly sensitive amyloid seeding assays. The lack of symptoms in these offspring indicates covert prion transmission from mother to offspring, resulting in a potential silent-carrier status. As for our studies to further the understanding of the mechanisms behind this transmission, we identified CWD-prions in reproductive and mammary tissue, and spleen of Tg(CerPrP-E226) mouse mothers as early as 72 days post inoculation. In addition, we found minute quantities of amyloid conversion material in placenta and fetal tissues from mother:offspring pairs at varying timepoints in CWD-infection. We were unable to detect prions in milk collected from CWD-positive transgenic dams, leading us to hypothesize that the route of TSE transmission to offspring is likely a combination of environmental exposure, and/or very low concentrations of prions breaching the feto-maternal interface.